Renal Inflammation in DOCA-Salt Hypertension: Role of Renal Nerves and Arterial Pressure - Banek, Christopher T. (Hypertension, 2019)
Recent reports indicate that, in addition to treating hypertension, renal denervation (RDN) also mitigates renal inflammation. However, since RDN decreases renal perfusion pressure, it is unclear whether these effects are due to the direct effects of RDN on inflammatory signaling or secondary to decreased arterial pressure (AP). Therefore, this study was conducted to elucidate the contribution of renal nerves to renal inflammation in the DOCA-salt rat, a model in which RDN decreases AP and abolishes renal inflammation. In Experiment 1, we assessed the temporal changes in renal inflammation by measuring renal cytokines and AP in DOCA-salt rats. Uninephrectomized (1K) adult male Sprague Dawley rats that received surgical renal denervation (RDN) or sham (Sham) were administered DOCA (100mg, s.c.) and 0.9% saline for 21 days. AP was measured by radiotelemetry, and urinary cytokine excretion were measured repeatedly. In Experiment 2, the contribution of renal nerves in renal inflammation was assessed in a 2-kidney DOCA-salt rat to control for renal perfusion pressure. DOCA-salt treatment was administered after unilateral (U-)RDN. In Experiment 1, DOCA-salt induced increases in AP and renal inflammation (assessed by urinary cytokines) were attenuated by RDN versus Sham. In Experiment 2, GRO/KC, MCP-1, and macrophage infiltration were lower in the denervated kidney vs. the contralateral Sham kidney. No differences in T-cell infiltration were observed. Together, these data support the hypothesis that renal nerves mediate, in part, the development of renal inflammation in the DOCA-salt rat independent of hypertension. The mechanisms and cell-specificity mediating these effects require further investigation.